Desarrollo de un sistema con Raspberry Pi y la Plataforma IoT Thingspeak para la identificación de las condiciones agroecológicas ‘‘Humedad, Radiación Solar y Temperatura’’ del cultivo de la Cholupa en la finca Don Pedro en la Ulloa (2021)
The cultivation of Cholupa is one of the productive bets of Huila and is a protagonist in the regional economy of the department, more than 2,000 hectares are planted annually with this delicious Passiflora. Through this work, which seeks to offer technological tools to producers of Cholupa in La Ulloa in the municipality of Rivera, an integrated IoT system was designed and implemented that allows the monitoring of key variables in the development of the crop such as Temperature, Humidity and UV Radiation.